Institutional capacity to generate and use evidence in LMICs: current state and opportunities for HPSR - Zubin Cyrus Shroff; Dena Javadi; Lucy Gilson; Rockie Kang; Abdul Ghaffar (BMC, 2017)
Abstract Background Evidence-informed decision-making for health is far from the norm, particularly in many low- and middle-income countries (LMICs). Health policy and systems research (HPSR) has an important role in providing the context-sensitive and -relevant evidence that is needed. However, there remain significant challenges both on the supply side, in terms of capacity for generation of policy-relevant knowledge such as HPSR, and on the demand side in terms of the demand for and use of evidence for policy decisions. This paper brings together elements from both sides to analyse institutional capacity for the generation of HPSR and the use of evidence (including HPSR) more broadly in LMICs. Methods The paper uses literature review methods and two survey instruments (directed at research institutions and Ministries of Health, respectively) to explore the types of institutional support required to enhance the generation and use of evidence. Results Findings from the survey of research institutions identified the absence of core funding, the lack of definitional clarity and academic incentive structures for HPSR as significant constraints. On the other hand, the survey of Ministries of Health identified a lack of locally relevant evidence, poor presentation of research findings and low institutional prioritisation of evidence use as significant constraints to evidence uptake. In contrast, improved communication between researchers and decision-makers and increased availability of relevant evidence were identified as facilitators of evidence uptake. Conclusion The findings make a case for institutional arrangements in research that provide support for career development, collaboration and cross-learning for researchers, as well as the setting up of institutional arrangements and processes to incentivise the use of evidence among Ministries of Health and other decision-making institutions. The paper ends with a series of recommendations to build institutional capacity in HPSR through engaging multiple stakeholders in identifying and maintaining incentive structures, improving research (including HPSR) training, and developing stronger tools for synthesising non-traditional forms of local, policy-relevant evidence such as grey literature. Addressing challenges on both the supply and demand side can build institutional capacity in the research and policy worlds and support the enhanced uptake of high quality evidence in policy decisions.